Urban wage behavior and food price inflation: the case of Ethiopia - Headey, Derek D.; Bachewe, Fantu Nisrane; Worku, Ibrahim; Dereje, Mekdim; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2012)
On the back of both a global food crisis and various domestic factors, Ethiopia has experienced one of the world’s fastest rates of food inflation in recent years. Yet the lack of high frequency survey data means that very little is known about the welfare impacts of these price changes. This study attempts to fill that knowledge gap using a unique monthly series of casual wages from 119 locations in both Ethiopian cities and rural towns. We use this data for two types of analysis. First, we construct a set of “poor person’s price indices” which we then use to deflate the daily laborer wage series in an effort to gauge the welfare trends among the urban poor. Second, we conduct formal econometric tests of whether changes in nominal wages respond to changes in food and non-food prices. We find alarming results. The disposable income of daily laborer’s declined sharply as food prices soared in 2007–2008, and there is neither descriptive nor econometric evidence that wages substantially adjust to higher food prices, except in the long run.